Características de las fracturas expuestas en pacientes del Hospital General Isidro Ayora - Íñiguez Zaruma, Nathaly Gissell (2021)
Exposed fractures are defined as the loss of bone continuity and exposure of the fracture site to the environment. Due to the fact that they constitute orthopedic emergencies, this research was proposed with the objective of characterizing them considering their frequency, age and sex in which they occur most frequently; and also to identify the characteristics of exposed fractures according to the degree of exposure according to the classification of Gustilo and Anderson, as well as the mechanism and location of the injury, hospitalization time, number of surgeries performed and the type of fixation used. For this purpose, a restrospective, descriptive, non-experimental, cross-sectional design was carried out in a population of 216 patients hospitalized in the Orthopedics and Traumatology Service of the Hospital General Isidro Ayora in the city of Loja, in the period April 2019-May 2020, of which 68 met the inclusion criteria. According to the research, exposed fractures mostly occurred in young people from 18 to 28 years old, the sex where it occurred more frequently was in men, and, considering the Gustilo and Anderson Classification, Type II was the most frequent, these exposed fractures were caused mainly by direct mechanism and were located in the tibia with an approximate length of hospital stay of 6 to 10 days for which surgery was performed; to resolve the fracture, internal fixation was used for the most part. Key words: bone, fracture, orthopedics, fixation, surgery